Sistem Pendukung Keputusan Penentuan Pengangkatan Karyawan Kontrak Menjadi Karyawan Tetap Menerapkan Metode Preference Selection Index (PSI) - Bani, Alexius Ulan; Prambodo, Yoga Listi; Azlan, Azlan (Building of Informatics, Technology and Science (BITS), 2022)
Employees are the main and most important element in the running of a company. The quality of employees is a determinant of how an employee's foundation is. In order to improve the quality of each employee, it is necessary to separate employees, between contract employees and permanent employees. the large number of employees may make the management confused in determining who should be made permanent employees. Therefore, a system is needed that can assist the government in selecting permanent employees. The system is a decision support system. A decision support system is a system where the process is carried out using a unified system with a method or more than 1 (one) method that is carried out using a computer base. SPK is used to assist certain elements in choosing or making a decision. Many methods can be used in DSS, in this study the PSI method was used. PSI is a method used in solving problems where the problem has many alternative choices of attributes. With this study, the results were that the best alternative was Dicky as an alternative B15 with a value of 0.8977, which in the end was suggested to be a permanent employee